Colorimetric pH-responsive and hemostatic hydrogel-based bioadhesives containing functionalized silver nanoparticles - Elham Khadem; Mahshid Kharaziha; Sahar Salehi (Materials Today Bio, 2023)
Here we develop and characterize a dual-cross-linked pH-responsive hydrogel based on the carboxyethyl chitosan-oxidized sodium alginate (CAO) containing silver nanoparticles (Ag NPs) functionalized with tannic acid/red cabbage (ATR). This hybrid hydrogel is formed via covalent and non-covalent cross-linking. The adhesive strength measured in contact with cow skin and compression strength is measured more than 3 times higher than that of CAO. Importantly, the incorporation of 1 ​wt% ATR into CAO significantly enhances the compression strength of CAO from 35.1 ​± ​2.1 ​kPa to 97.5 ​± ​2.9 ​kPa. Moreover, the cyclic compression tests confirm significantly higher elastic behavior of CAO after the addition of ATR-functionalized NPs to CAO. The CAO/ATR hydrogel is pH-sensitive and indicated remarkable color changes in different buffer solutions. The CAO/ATR also shows improved hemostatic properties and reduced clotting time compared to the clotting time of blood in contact with CAO hydrogel. In addition, while CAO/ATR is effective in inhibiting the growth of both Gram-positive and Gram-negative bacteria, CAO is only effective in inhibiting the growth of Gram-positive bacteria. Finally, the CAO/ATR hydrogel is cytocompatible with L929 fibroblasts. In summary, the resulting CAO/ATR hydrogel shows promising results in designing and constructing smart wound bioadhesives with high cytocompatibility, antibacterial properties, blood coagulation ability, and fast self-healing properties.